Virtual instrumentation application for symmetrical and asymmetrical text encryption/decryption studying - Teodorescu, R. M.; Lita, I.; Cioc, I. B.; Visan, D. A. (2015 7th International Conference on Electronics, Computers and Artificial Intelligence (ECAI), 2015)
This paper presents a software application for studying of the most used methods for text encryption/decryption, with utilization in teaching activities and didactical laboratories. The applications is realized using virtual instrumentation software and was designed as a didactical software platform for studying and analyze the two of the most used encryption techniques, the symmetrical and asymmetrical encryption algorithms. These encryption and decryption techniques are applied to encrypt and then decrypt a given text, for an easily understanding and verification of the encrypting/decrypting techniques implemented. The main aspects of encryption techniques can be analyzed, like the text encryption strength as well as the complexity of algorithm implementation and processing resources involved. Because of the advantages of visual programming languages like LabVIEW, users can easily understand programming techniques for different encryption/decryption methods and data manipulation, and they can modify the application to add new functionalities or to implement other algorithms.